2017
DOI: 10.1371/journal.pone.0185974
|View full text |Cite
|
Sign up to set email alerts
|

Genetic and ecological insights into glacial refugia of walnut (Juglans regia L.)

Abstract: The distribution and survival of trees during the last glacial maximum (LGM) has been of interest to paleoecologists, biogeographers, and geneticists. Ecological niche models that associate species occurrence and abundance with climatic variables are widely used to gain ecological and evolutionary insights and to predict species distributions over space and time. The present study deals with the glacial history of walnut to address questions related to past distributions through genetic analysis and ecological… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
32
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(41 citation statements)
references
References 75 publications
3
32
0
1
Order By: Relevance
“…We confirmed in this study previous results showing genetic structure within the wild Prunus armeniaca populations in Central Asia, with a highly differentiated Kyrgyz population in the South (red cluster, Decroocq et al, 2016). Such genetic structure is probably related to glacial refugia for P. armeniaca in South Central Asia (Aradhya et al, 2017), followed by a recolonization of the Northern territories, Thanks to more extensive sampling compared to previous studies, we could infer the wild apricot evolutionary history in China. We found high genetic differentiation between the different Armeniaca species, P. armeniaca, Prunus sibirica and Prunus mume.…”
Section: Diversification Of Wild Apricots In Central and Eastern Asiasupporting
confidence: 90%
See 1 more Smart Citation
“…We confirmed in this study previous results showing genetic structure within the wild Prunus armeniaca populations in Central Asia, with a highly differentiated Kyrgyz population in the South (red cluster, Decroocq et al, 2016). Such genetic structure is probably related to glacial refugia for P. armeniaca in South Central Asia (Aradhya et al, 2017), followed by a recolonization of the Northern territories, Thanks to more extensive sampling compared to previous studies, we could infer the wild apricot evolutionary history in China. We found high genetic differentiation between the different Armeniaca species, P. armeniaca, Prunus sibirica and Prunus mume.…”
Section: Diversification Of Wild Apricots In Central and Eastern Asiasupporting
confidence: 90%
“…We confirmed in this study previous results showing genetic structure within the wild Prunus armeniaca populations in Central Asia, with a highly differentiated Kyrgyz population in the South (red cluster, Decroocq et al, ). Such genetic structure is probably related to glacial refugia for P. armeniaca in South Central Asia (Aradhya et al, ), followed by a recolonization of the Northern territories, including the Kazakh Tian Shan ranges, upon global warming. ABC analyses further confirmed that the yellow wild P. armeniaca populations in Central Asia recently diverged from the red wild P. armeniaca populations in Kyrgyzstan.…”
Section: Discussionmentioning
confidence: 99%
“…The difficulty of estimating the native distribution arises also in other cultivated medio-European trees that are not only present in the Mediterranean region. It exists indeed conflicting results between an ecological niche model projecting a significant presence of walnut (Juglans regia) in the Balkan Peninsula during the LGM in contrast to genetic analysis that suggest refugia in Southwest Asia (Aradhya et al 2017). For another key cultivated tree, the chestnut (Castanea sativa), a paleodistribution modelling approach validated with pollen and charcoal records (Roces-Díaz et al 2018) seems to be in agreement with a phylogeographical analysis (Mattioni et al 2013): LGM refugia were suggested in the north of the Iberian and Italian peninsulas, in Greece, and along the southern coast of the Black Sea.…”
Section: The Complex Native Status Of Domesticated or Useful Mediterrmentioning
confidence: 99%
“…The native range of common walnut is uncertain, but (apparently) wild populations grow in isolated favorable habitats across a wide geographical range from China to the Iberian Peninsula ( Manning, 1978 ; Draine and Hiden, 1998 ; Beer et al, 2008 ; Martínez-García et al, 2016 ; Pollegioni et al, 2017 ). Because of continued uncertainty concerning the number and locations of refugia for J. regia , current populations may or may not have been derived from refugia in Southern Europe, the Balkans, the Carpathian mountains, Anatolia, the Zagros mountains, and even China ( Martínez-García et al, 2016 ; Aradhya et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…This road led westward along the northern foothills of the Eastern Tien Shan Mountains. It connected Eastern China (Shandong province) and Western China (Eastern Tien Shan mountains; Urumqi; Xinjiang province), facilitating cultural and agrarian exchange ( Christian, 2000 ; Aradhya et al, 2017 ; Pollegioni et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%